Studies on Physico-chemical analysis of Mohabala Lake near Bhadrawati, District - Chandrapur (MS), India - Mahajan VS; Pokale SS (International Journal of Life Sciences, 2017)
The Mohabala lake is principal fresh water body located within Bhadrawati tahsil in Chandrapur District of Maharashtra state. Now a day lakes are degraded by both natural and anthropogenic activities, which deteriorate their quality of lake water. Normally, lakes perform the functions directly related to their physical, chemical and biological integrity to decide quality status of water. The analysis of various physico-chemical characteristics of water quality of Mohobala lake at different sites under study viz. Site A, Site B and Site C were carried out for two years i.e. from June 2013 to May 2015 for the detection of level of pollution, physic-chemical parameters analysis like, Atmospheric temperature (°C), Water temperature (°C), Transparency (cm.), Conductivity (μmhos/cm.), pH, D.O. (mg/lit.), Free CO2 (mg/lit.), Total alkalinity (mg/lit.), Phenolphthalein alkalinity (mg/lit.), Total hardness (mg/lit.), Calcium hardness (mg/lit.), Magnesium hardness (mg/lit.), Chloride (mg/lit.), B.O.D. (mg/lit.), C.O.D. (mg/lit.), Phosphate (mg/lit.), Sulphate (mg/lit.), Nitrate (mg/lit), Total solids (mg/lit.). Total dissolved solids (mg/lit.), Total suspended solids (mg/lit.).